Dynamic Changes in the Levels of Amyloid-β42 Species in the Brain and Periphery of APP/PS1 Mice and Their Significance for Alzheimer’s Disease - Zhang, Liding; Yang, Changwen; Li, Yanqing; Niu, Shiqi; Liang, Xiaohan; Zhang, Zhihong; Luo, Qingming; Luo, Haiming (Frontiers in Molecular Neuroscience, 2021)
Although amyloid-β42 (Aβ42) have been used as one of the core biomarkers for the diagnosis of AD, the dynamic changes in the levels of its different forms in the brain, blood, and even intestines and their correlation with the progression of Alzheimer’s disease (AD) disease remain obscure. Herein, we screened Aβ42-specific preferred antibody pairs 1F12/1F12 and 1F12/2C6 for accurate detection of Aβ42 species including total Aβ42, Aβ42 oligomers (Aβ42Os), and Aβ42 monomers (Aβ42Ms) with sandwich ELISA. The levels of Aβ42 species in the brain, blood, and intestines of different aged APP/PS1 mice were quantified to study their correlation with the progression of AD. Although total Aβ42 level in the blood was not correlated with the progression of AD, a significant decrease of Aβ42Ms level and increase of Aβ42Os level in the blood and prominently elevated levels of Aβ42Os in the brains were observed in APP/PS1 mice from 3-month-old to 9-month-old, demonstrating the correlation between the levels of Aβ42Ms and Aβ42Os in the blood and brain and the progression of AD. Over 3-fold higher of AβOs levels in the brain than that in intestines was found in 9-month-old APP/PS1 mice indicate that elevated Aβ levels in the gastrointestinal organs may originate from the brain and blood. Meanwhile, The gut microbiota composition changes with age in APP/PS1 mice were also observed. Therefore, elevated intestinal tissue-derived Aβ and the shift in microbiome composition could be used as a potential AD early diagnosis tool, and further used as an indicator for pharmacological interventions to reduce cerebral amyloid.